Power Factor Correction Boost Converter Based on the Three-State Switching Cell - Robles Balestero, Juan Paulo; Tofoli, Fernando Lessa; Fernandes, Rodolfo Castanho; Torrico-Bascope, Grover Victor; Seixas, Falcondes José Mendes [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2012)
The need for solid-state ac-dc converters to improve power quality in terms of power factor correction, reduced total harmonic distortion at input ac mains, and precisely regulated dc output has motivated the investigation of several topologies based on classical converters such as buck, boost, and buck-boost converters. Boost converters operating in continuous-conduction mode have become particularly popular because reduced electromagnetic interference levels result from their utilization. Within this context, this paper introduces a bridgeless boost converter based on a three-state switching cell (3SSC), whose distinct advantages are reduced conduction losses with the use of magnetic elements with minimized size, weight, and volume. The approach also employs the principle of interleaved converters, as it can be extended to a generic number of legs per winding of the autotrans-formers and high power levels. A literature review of boost converters based on the 3SSC is initially presented so that key aspects are identified. The theoretical analysis of the proposed converter is then developed, while a comparison with a conventional boost converter is also performed. An experimental prototype rated at 1 kW is implemented to validate the proposal, as relevant issues regarding the novel converter are discussed.
Keywords: AC-DC converters; boost converter; harmonics; power factor correction (PFC); three-state switching cell (3SSC)